Analysing Industrial Interconnection in Improving Batam City’s Economic Development - Elinda Nurul Hasana Dewi B. S.; Irene Juwita Depari; Nina Pramita; Intania Syafrina; Tiara Annisah (International Journal Labs, 2022)
One of the factors for increasing economic growth is the increase in Gross Regional Domestic Product (GRDP). The case study used the city of Batam. In this city, the contribution of the dependable sector is the manufacturing industry. In this study, the value of the contribution of the manufacturing industry sector to the increase in economic growth.